Investigating the Synergistic Interaction of Diabetes, Tobacco Smoking, Alcohol Consumption, and Hypercholesterolemia on the Risk of Pancreatic Cancer: A Case-Control Study in Italy. (29th April 2014) - La Torre, Giuseppe; Sferrazza, Antonella; Gualano, Maria Rosaria; de Waure, Chiara; Clemente, Gennaro; De Rose, Agostino Maria; Nicolotti, Nicola; Nuzzo, Gennaro; Siliquini, Roberta; Boccia, Antonio; Ricciardi, Walter
Abstract : The aims of the present research are to investigate the possible predictors of pancreatic cancer, in particular smoking status, alcohol consumption, hypercholesterolemia, and diabetes mellitus, in patients with histologically confirmed pancreatic carcinoma and to examine the synergism between risk factors. A case-control study (80 patients and 392 controls) was conducted at the Teaching Hospital "Agostino Gemelli" in Rome. A conditional logistic regression was used for the statistical analysis and results were presented as odds ratio (OR) and 95% confidence intervals (95% CI). We also investigated the possible interactions between risk factors and calculated the synergism index (SI). The multivariate analysis revealed that hypercholesterolemia and alcohol consumption resulted in important risk factors for pancreatic cancer even after the adjustment for all variables (OR: 5.05, 95% CI: 2.94–8.66; OR: 2.25, 95% CI: 1.30–3.89, resp.). Interestingly, important synergistic interactions between risk factors were found, especially between ever smoking status and alcohol consumptions (SI = 17.61) as well as alcohol consumption and diabetes (SI = 17.77). In conclusion, the study confirms that hypercholesterolemia and alcohol consumption represent significant and independent risk factors for pancreatic cancer. Moreover, there is evidence of synergistic interaction between diabetes and lifestyle factors (drinking alcohol and eating fatty foods).